2014
DOI: 10.1002/app.40486
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide nanofiber membranes functionalized with zinc phthalocyanines

Abstract: Electrospinning is an efficient method for the production of polyamide nanofiber membranes that are suitable for water filtration. Previous studies have shown that nanofiber membranes have high clean water permeability. The pathogen removal efficiency can be improved by functionalization with (organic) biocides. However, these membranes, like other membranes, are vulnerable to fouling which reduces the filtration efficiency. Therefore the present article investigates the potential of zinc phthalocyanines, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The absorption spectrum of the monoclinic structure (α-form) has a doublet around 708 and 653 nm, while in the tricyclic spectrum of the (β-form) a high intensity band is observed at 646 nm with two shoulders at 620 and 665 nm [51]. Finally, the B-band is within the UV region of the spectrum, at around 340 nm [6,28,29,30], and it refers to the electronic n- π * transitions between the molecules. The B-band is due to a2u(π)eg(π*) together with b2u(π)eg(π*) transitions [52,53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption spectrum of the monoclinic structure (α-form) has a doublet around 708 and 653 nm, while in the tricyclic spectrum of the (β-form) a high intensity band is observed at 646 nm with two shoulders at 620 and 665 nm [51]. Finally, the B-band is within the UV region of the spectrum, at around 340 nm [6,28,29,30], and it refers to the electronic n- π * transitions between the molecules. The B-band is due to a2u(π)eg(π*) together with b2u(π)eg(π*) transitions [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…Electrospun fibres, as a support material, have been used by Mafukidze et al and resulted in a lack of mechanical strength, which polyamides membranes employed in this work may possess [ 11 ]. Therefore, introducing MPcs as molecular materials whiting a polymer, such as Nylon 11, could promote outstanding and effective properties in membrane applications and cause them to remain intact in the fiber [ 11 , 24 , 25 , 26 , 27 , 28 , 29 ]. We report in this communication the fabrication of semiconductor membranes consisting of MgPc-allenes particles dispersed in Nylon 11 films.…”
Section: Introductionmentioning
confidence: 99%
“…The immobilized conjugate was active as a photocatalyst for oxidizing organic pollutants, such as 4-chlorophenol and Orange G using oxygen as an oxidant. Interestingly, Goethals et al[112] reported that PA-6 membranes functionalized with [2,9,16,23-tetra(2-thioquinoline)phthalocyaninato]zinc(II)) after the electrospinning deposition were capable of photobleaching significantly more DPBF than membranes that were non functionalized.Polystyrene electrospun fibers were also employed as they have extensive π-π electronic interactions between the aromatic systems of the phthalocyanine and the polymer[105,106,107,108]. All the unsymmetrically substituted complexes showed antimicrobial activity towards S. aureus under illumination with visible light.…”
mentioning
confidence: 99%
“…Surprisingly, among the other potential photoinitiators described in the literature, the use of phthalocyanine (Pc) derivatives are barely investigated despite their excellent light absorption properties at λ > 400 nm. Pcs have attracted increasing research interest in medicine, organic semiconductors, nonlinear optics, memory devices, and as photocatalysts for the degradation of organic dyes, photodynamic therapy agents, and sensors together with high chemical and thermal stabilities. According to their high singlet oxygen production under visible light exposure, Pcs were also used in the synthesis of photobactericidal materials using electrospinning techniques and appear as promising candidates for the development of new efficient antimicrobial materials. The variation of substituents and axial ligands on the Pcs’ chemical backbone as well as the metal ion in its cavity results in a wide range of structures, thereby allowing the fine-tuning of their physicochemical characteristics. Despite the amazing panel of Pc derivative structures described in the literature, few studies demonstrated their ability to initiate the FRP and no investigations regarding the cationic photopolymerization of epoxides by Pc-derivative photoinitiating systems were reported.…”
Section: Introductionmentioning
confidence: 99%